A Review of Immunomodulatory Reprogramming by Probiotics in Combating Chronic and Acute Diabetic Foot Ulcers (DFUs) - Prakhar Srivastava; Tesalonika Sondak; Karthikeyan Sivashanmugam; Kwang-sun Kim (MDPI AG, 2022)
Diabetic foot ulcers (DFUs) are characterized by a lack of angiogenesis and distal limb diabetic neuropathy. This makes it possible for opportunistic pathogens to protect the biofilm-encased micro-communities, causing a delay in wound healing. The acute and chronic phases of DFU-associated infections are distinguished by the differential expression of innate proinflammatory cytokines and tumor necrosis factors (TNF-α and -β). Efforts are being made to reduce the microbial bioburden of wounds by using therapies such as debridement, hyperbaric oxygen therapy, shock wave therapy, and empirical antibiotic treatment. However, the constant evolution of pathogens limits the effectiveness of these therapies. In the wound-healing process, continuous homeostasis and remodeling processes by commensal microbes undoubtedly provide a protective barrier against diverse pathogens. Among commensal microbes, probiotics are beneficial microbes that should be administered orally or topically to regulate gut-skin interaction and to activate inflammation and proinflammatory cytokine production. The goal of this review is to bridge the gap between the role of probiotics in managing the innate immune response and the function of proinflammatory mediators in diabetic wound healing. We also highlight probiotic encapsulation or nanoformulations with prebiotics and extracellular vesicles (EVs) as innovative ways to tackle target DFUs.